Generation of a pair of independently binding DNA aptamers in a single round of selection using proximity ligation1. Issue 43 (28th May 2015) - Chumphukam, O.; Le, T. T.; Piletsky, S.; Cass, A. E. G.
<x xml:space="preserve">Abstract</x> The ability to rapidly generate a pair of aptamers that bind independently to a protein target would greatly extend their use as reagents for two site ('sandwich') assays.